2016
DOI: 10.1021/acs.jproteome.6b00076
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Metabolic Signature of Human Bladder Cancer Cells Carrying an Impaired Fanconi Anemia Tumor-Suppressor Signaling Pathway

Abstract: Metabolic profiling has great potential to help the diagnosis and prognosis of cancer patients. Fanconi Anemia (FA) tumor suppressor signaling has been instrumental in understanding human-tumorigenesis. However, this instrumental understanding has never been demonstrated at the metabolic level. Here we show that impaired FA signaling can lead cells to exhibit metabolic signatures of tumorigenesis. This is consistent with our original studies of the roles of FA signaling in suppressing non-FA tumorigenesis at f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…As accumulated studies have indicated, malfunctioned FA genes and proteins have been found to be associated with a variety of cancer patients who do not have FA (Table 1). For the first time, our studies have evidently shown that an impaired FA pathway is associated with the development of human cancer, and the altered pathway can promote the development of non-FA human cancer[1821]. These findings further support the general tumor suppressor roles played by the FA proteins.…”
Section: The Fa Pathway: a Tumor Suppressor Signaling Networksupporting
confidence: 63%
See 1 more Smart Citation
“…As accumulated studies have indicated, malfunctioned FA genes and proteins have been found to be associated with a variety of cancer patients who do not have FA (Table 1). For the first time, our studies have evidently shown that an impaired FA pathway is associated with the development of human cancer, and the altered pathway can promote the development of non-FA human cancer[1821]. These findings further support the general tumor suppressor roles played by the FA proteins.…”
Section: The Fa Pathway: a Tumor Suppressor Signaling Networksupporting
confidence: 63%
“…As a result, 18 metabolites, which represent the end products of cell proliferation and/or apoptosis, were found to be significantly different between FAVL-high and -low cells. Methionine, phenylalanine and threonine, resulting from a tumorigenic process, were substantially increased in FAVL-high cells (FA signaling compromised cells) [21]. With this study, characterization on the tumor-promotion roles of aberrant FA signaling in the development of human cancer in the general population was achieved at the genomic, functional, as well as the metabolic levels.…”
Section: Fa Signaling and Metabolismmentioning
confidence: 99%
“…Following the functional demonstration of impaired FA signaling contributing to the development of human cancer in patients without FA, [41][42][43] the genetics and metabolomics studies further confirmed this unique role in promoting formation of human cancers, 40,44,45 including breast cancer, for the general population. BRCAs are widely accepted to be important tumor suppressors before the term of the (canonical) FA signaling pathway, which was seemingly fine for studying their individual roles in DNA damage repair.…”
Section: Implications Of Fa Signaling In Etiology and Treatment Of Brmentioning
confidence: 87%
“…This marked us being the first to have achieved characterization of the general tumor suppressor functions of the FA signaling pathway at all three levels, genetically 46 , functionally 47 as well as metabolically 45 . The significance of FA signaling is further supported by the occurrence of the impaired FA pathway in human cancers, in which there is about 30–50% of tumors carrying a defective signaling network at the genetic level alone.…”
Section: Discussionmentioning
confidence: 99%